(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The issue of financing in contemporary economies is the vital issue in achieving and sustaining economic growth by ensuring increasing rates of effective investment, and here comes the role of the central bank to fill the void left by the lack of resources, weak production, and low levels of economic surplus in emerging and young developing economies, and for the purpose of identifying the role of the bank. In maintaining investment rates, we decided to study financing strategies for it in terms of goals, incentives, and mechanisms, so that the economy has an acceptable pattern of interaction between the real and symbolic economies, so that the monetary cycle in turn becomes an effective mechanism for generating economic surplus and ensuring its productive investment. Our study started from the hypothesis that the central bank is the most efficient source capable of providing various sources of financing for investment operations that guarantee the sustainability of economic growth. We divided the study of this topic into three sections: First: Developing economies: features and mechanisms of development. Second: The role of investment in sustaining economic growth in the economies of developing countries. Third: Investment financing between motives and objectives and the effectiveness of motivating roles in the Iraqi economy.